Altered blood gas tensions of oxygen and carbon dioxide confound coronary reactivity to apnea - Fischer, Kady; Guensch, Dominik P.; Shie, Nancy; Nadeshalingham, Gobinath; Lebel, Julie; Friedrich, Matthias G. (Frontiers in Anesthesiology, 2022)
Purpose: Arterial blood gases change frequently during anesthesia and intensive care. Apnea can occur during diagnostic exams and airway and surgical interventions. While the impact of blood gas levels on coronary blood flow is established, their confounding effect on coronary vasoreactivity in response to an apneic stimulus especially in coronary artery disease is not known. Methods: Six anesthetized control swine and eleven swine with a coronary artery stenosis were examined. Nine different blood gas levels from a combination of arterial partial pressure of oxygen (70, 100 and 300mmHg) and carbon dioxide (30, 40 and 50mmHg) were targeted. Apnea was induced by halting controlled positive pressure ventilation for 3-30s, while left descending coronary artery flow was measured and reported relative to apnea duration, and at the adjusted mean (12s). Results: At normoxemic-normocapnic blood gas levels, apnea increased coronary blood flow in proportion to the duration of apnea in the control (r=0.533, p<0.001) and stenosed groups (r=0.566, p<0.001). This culminated in a 42% (95%CI: 27-58) increase in controls (p<0.001) and, to a lesser extent, 27% (15-40) in the presence of coronary artery stenosis (p<0.001). Vasoreactivity was augmented by mild-hypoxemic levels (81% (65-97), and 66% (53-79) increase in flow respectively, p<0.001 vs. normoxemia), but markedly reduced during hyperoxia (7.5% (-8.2-23) and 0.3% (-12-13), respectively, p<0.001 vs. normoxemia). Conclusion: Alterations of blood oxygen and carbon dioxide affect coronary vascular reactivity induced by apnea in swine, which was attenuated further in the presence of a coronary stenosis. Especially hyperoxia significantly reduces coronary blood flow and blunts coronary vascular reactivity.